The Influence of Time Pressure and Brand Personality on Impulsive Buying Among Generation Z: Local Indonesian Skincare Brands - Fadilah, Firsty Yulehinin Ditha; Hapsari, Raditha Dwi Vata; Yulianti, Ida (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This research investigates the influence of hedonic motivations, time constraints, and brand personality on impulsive purchasing behaviour, specifically within the context of online consumer activity. The study employs Partial Least Squares (PLS) Structural Equation Modelling (SEM) to examine data from 250 participants. The study's results indicate that hedonic incentives substantially moderate the connection between brand personality and impulsive purchasing behaviour, as well as between time constraints and impulsive purchase. The findings indicate that brand personality and time pressure both positively affect impulsive purchasing, with hedonic motives serving as a crucial mediator. These findings offer significant insights for marketers seeking to enhance consumer engagement in online shopping environments by emphasizing emotional and time-sensitive purchasing triggers. The research enhances the existing literature by expanding the understanding of impulsive buying behavior in the digital age and suggests practical strategies for e-commerce businesses to drive sales.